2013
DOI: 10.1158/0008-5472.can-11-1433
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Triggers Hedgehog-Mediated Tumor–Stromal Interactions in Pancreatic Cancer

Abstract: Pancreatic cancer is characterized by a desmoplastic reaction that creates a dense fibroinflammatory microenvironment, promoting hypoxia and limiting cancer drug delivery due to decreased blood perfusion. Here we describe a novel tumor-stroma interaction that may help explain the prevalence of desmoplasia in this cancer. Specifically, we found that activation of HIF-1α by tumor hypoxia strongly activates secretion of the sonic hedgehog ligand SHH by cancer cells which in turn causes stromal fibroblasts to incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 49 publications
10
137
0
Order By: Relevance
“…Gene expression analyses suggested that only murine stroma but not tumor epithelium could respond to SMO antagonist explaining the lack of response in vitro (12,13). Coculture experiments further showed the paracrine activation of Hh signaling in lung and pancreatic cancer (14,15). These highlight the importance of Hh signaling in tumor and thus serve as a rational for a treatment targeting cancer (11).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Gene expression analyses suggested that only murine stroma but not tumor epithelium could respond to SMO antagonist explaining the lack of response in vitro (12,13). Coculture experiments further showed the paracrine activation of Hh signaling in lung and pancreatic cancer (14,15). These highlight the importance of Hh signaling in tumor and thus serve as a rational for a treatment targeting cancer (11).…”
Section: Introductionmentioning
confidence: 91%
“…We therefore focused on the effects of vismodegib in stroma to understand the mechanisms leading to the reduced proliferation hence tumor growth delay. Previous experiments suggest that antagonization of Hh pathway in fibroblasts reduces the production of ECM, cytokines, and growth factors (13)(14)(15). Therefore, we analyzed mRNA levels of the ECM molecules Fibronectin (Fn1) and Collagen (Col1a2).…”
Section: Treatment With Vismodegib Causes Downregulation Ofmentioning
confidence: 99%
“…Hh signaling plays an important role in the initiation and progression of pancreatic cancer (15). As shown in Fig.…”
Section: Effects Of Curcumin On the Expression Of Hypoxia-modulated Ementioning
confidence: 99%
“…Pancreatic cancer is characterized by extensive desmoplasia that is caused by the dense stromal fibroinflammatory reaction of fibroblasts, which leads to a reduced nutrient and oxygen supply, resulting in a severe hypoxic tumor microenvironment (9,10). To adapt and survive in this hostile environment, cancer cells must rely on their ability to reprogram canonical metabolic pathways to ensure that their needs for macromolecule synthesis and essential energy demands are met (11,12).…”
Section: Introductionmentioning
confidence: 99%